The Kelayakan Politik Peraturan Tentang Preventif Dan Tindak Lanjut Terhadap Pelecehan Seksual Di Perguruan Tinggi - Suharno, Suharno; Milwan, Milwan; Rifai, Rifai (Jayapangus Press, 2024)
The urgency of this research pertains to the political feasibility of Minister of Education and Culture Regulation No. 30/2021 regarding the Prevention and Handling of Sexual Violence (PPKS) in the University Environment due to the emergency situation of sexual violence on campus. This study not only highlights the extent to which the policy is acceptable to decision-makers and the general public but also underscores the importance of ensuring that any enacted policy has strong political support and does not generate controversy. The research methodology involves detailed analysis of existing regulations, gathering readings from books, academic journals, electronic media news, and conducting interviews with various stakeholders to gather their views on the political feasibility of the regulation. The findings indicate that the enactment of the regulation initially elicited diverse reactions from the public, with clear pros and cons. From different perspectives, particularly concerning various interests, the public voiced protests and controversies regarding the implications and impacts of the regulation. While supporters perceive it as a positive step in providing protection for the entire university community, with expected preventive measures and effective handling of sexual harassment cases, opponents view it as potentially promoting adultery and LGBT issues, especially from a religious standpoint. Nonetheless, it is crucial for the public to regard this regulation as a formal public policy, established based on an understanding and handling of societal issues.